2008
DOI: 10.1002/uog.6126
|View full text |Cite
|
Sign up to set email alerts
|

Maternal endothelial function and serum concentrations of placental growth factor and soluble endoglin in women with abnormal placentation

Abstract: Objectives To determine whether maternal serum concentrations of placental growth factor (PlGF) PlGF (154.8 ± 150.8 vs. 423.3 ± 230.5 pg/mL; P < 0.001) (data given as mean ± SD) and higher levels of sEng (8.1 (7.0-14.1) vs. 6.5 (4.9-7.9)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 53 publications
3
37
0
2
Order By: Relevance
“…Thus, there is similarity between the observations made with flow cytometry in these "Great Obstetrical Syndromes", and those that we report by examining the concentrations of angiogenic and anti-angiogenic factors (e.g. preeclampsia [38][39][40][41][42][43][44][45][47][48][49][50][51][52][53][54][55][56], pregnancies with SGA fetuses and abnormal Doppler velocimetry [57][58][59], "mirror syndrome" [61], TTTS [62] and unexplained fetal death [63].…”
Section: Clinical Implicationsupporting
confidence: 76%
See 2 more Smart Citations
“…Thus, there is similarity between the observations made with flow cytometry in these "Great Obstetrical Syndromes", and those that we report by examining the concentrations of angiogenic and anti-angiogenic factors (e.g. preeclampsia [38][39][40][41][42][43][44][45][47][48][49][50][51][52][53][54][55][56], pregnancies with SGA fetuses and abnormal Doppler velocimetry [57][58][59], "mirror syndrome" [61], TTTS [62] and unexplained fetal death [63].…”
Section: Clinical Implicationsupporting
confidence: 76%
“…Elevated plasma sEng concentrations have been reported in obstetrical conditions with perturbation of blood supply to the uterus such as preeclampsia [38][39][40][41][42][43][44][45]48,49,51,52,56], and pregnancies with fetal growth restriction [57][58][59]. Evidence suggests that over-expression of Eng on trophoblasts could inhibit trophoblast differentiation and invasion during placentation [85,86].…”
Section: Plasma Concentrations Of Pro-angiogenic and Anti-angiogenic mentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21][22][23][24][25] Together with endothelial dysfunction, these have become the biochemical hallmarks of severe preeclampsia. Few studies have investigated the functions of CSE/H 2 S in pregnancy.…”
mentioning
confidence: 99%
“…47,48 In line with these observations, numerous studies have concluded that women who subsequently develop PE demonstrate impaired endothelium-dependent vasodilation early in pregnancy. 8,49,50 Abnormal vascular function has been shown to persist postpartum after PE, and it may provide an explanation for the significant risk of cardiovascular disease later in life. 8,10,12 Indeed, an important outstanding question is whether abnormal endothelial biology is a cause or a consequence of PE disorders.…”
Section: Vascular Dysfunction In Pementioning
confidence: 99%